Risk of late-onset depression and cognitive decline: results from inflammatory proteome analyses in a prospective population-based cohort study - Perna, Laura; Trares, Kira; Perneczky, Robert; Tato, Maia; Stocker, Hannah; Möllers, Tobias; Holleczek, Bernd; Schöttker, Ben; Brenner, Hermann (American journal of geriatric psychiatry, 2022)
Objective - Research suggests that inflammation is linked to both late-onset depression (LOD) and cognitive decline, and that LOD might have biological underpinnings differentiating it from recurrent depression. Evidence from inflammatory proteome analyses in large prospective cohorts is scarce. The aim of this study was to assess whether and which inflammation-related biomarkers are associated with LOD, recurrent depression, and cognitive decline due to vascular pathology (vascular dementia). - Design - Ongoing population-based cohort study of older adults followed for up to 17 years with regard to clinical diagnosis of various age-related diseases (ESTHER study, n = 9,940). - Setting - Longitudinal cohort started in 2000-2002 in a community setting in Saarland, a southwestern German state. - Participants - Subgroup of randomly selected participants of the ESTHER study (n = 1,665). - Measurements - Inflammatory biomarkers were measured with the Olink Target 96 in baseline samples. - Results - Out of 78 biomarkers interleukin 10 (IL-10) and C-C chemokine ligand 4 (CCL4) were associated with significantly increased risk of LOD after multiple testing correction. Hazard ratios (95-confidence interval) per 1 standard deviation increase were 1.37 (1.15-1.63) for IL-10 and 1.34 (1.13-1.59) for CCL4. None of the inflammatory markers was associated with recurrent depression. The dose-response analysis showed a similar monotonic risk increase for LOD and vascular dementia with increasing IL-10 levels. - Conclusion - These results suggest that inflammatory markers are involved in the etiology of LOD, but not of recurrent depression and that LOD and vascular dementia might share common inflammatory etiology with respect to IL-10.
Online veröffentlicht: 3. Dezember 2021
Gesehen am 25.09.2022